Assessment of the Angiogenic Potential of 2-Deoxy-D-Ribose Using a Novel in vitro 3D Dynamic Model in Comparison With Established in vitro Assays - Dikici, Serkan; Aldemir Dikici, Betül; Bhaloo, Shirin Issa; Balcells, Mercedes; Edelman, Elazer R.; MacNeil, Sheila; Reilly, Gwendolen C.; Sherborne, Colin; Claeyssens, Frederik (Frontiers in Bioengineering and Biotechnology, 2020)
Angiogenesis is a highly ordered physiological process regulated by the interaction of endothelial cells with an extensive variety of growth factors, extracellular matrix components and mechanical stimuli. One of the most important challenges in tissue engineering is the rapid neovascularization of constructs to ensure their survival after transplantation. To achieve this, the use of pro-angiogenic agents is a widely accepted approach. The study of angiogenesis has gained momentum over the last two decades. Although there are various in vitro, ex vivo and in vivo angiogenesis models that enable testing of newly discovered pro-angiogenic agents, the problem with researching angiogenesis is the choice of the most appropriate assay. In vivo assays are the most representative and reliable models, but they are expensive, time-consuming and can cause ethical concerns whereas in vitro assays are relatively inexpensive, practical and reproducible, but they are usually lack of enabling the study of more than one aspect of angiogenesis, and they do not fully represent the complexity of physiological angiogenesis. Therefore, there is a need for the development of an angiogenesis model that allows the study of angiogenesis under physiologically more relevant, dynamic conditions without causing ethical concerns. Accordingly, in this study, we developed 3D in vitro dynamic angiogenesis model, and we tested the angiogenic potential of 2-deoxy-D-ribose (2dDR) in comparison with vascular endothelial growth factor (VEGF) using newly developed in vitro 3D dynamic model and well established in vitro models. Our results obtained using conventional in vitro assays demonstrated that 2dDR promoted proliferation, migration and tube formation of human aortic endothelial cells (HAECs) in a dose-dependent manner. Then, the angiogenic activity of 2dDR was further assessed using the newly developed 3D in vitro model, which enabled the monitoring of cell proliferation and infiltration simultaneously under dynamic conditions. Our results showed that the administration of 2dDR and VEGF significantly enhanced the outgrowth of HAECs and the cellular density under either static or dynamic conditions.